Small for Gestational Age as a Predictor of Behavioural and Learning Problems in Twins - Rooney, Rosanna; Hay, David; Levy, F. (Australian Academic Press Pty. Ltd, 2003)
The study examines the effects of being born small for gestational age (SGA) on rates of behavioural problems in twins and siblings, utilising data from the Australian Twin Study of disruptive behaviour disorders in twins and their siblings. Participants were 3944 twins and their siblings who were assessed at two intervals three years apart. At the first assessment (1991), they ranged between 4 and 12 years of age. Items assessing Attention Deficit /Hyperactivity Disorder were based on DSM-III-R criteria (Time 1) and DSM-IV criteria (Time 2). Other measures included history of speech and reading therapy, demographic information and obstetric and neonatal history. Results indicated that both male and female twins, who were extremely growth restricted (small for gestational age up to the third percentile-WGA3) showed more inattention, and poorer speech and reading scores. The effects were greater for males. Male twins who were small for gestation age, up to the10th percentile, were more likely to have a DSM-IV diagnosis of Inattention. Implications of these results included WGA3 male twins being at a 'triple disadvantage' for subsequent behavioural and learning problems, in that being male, being a twin and being small for gestational age are all significant factors. Recommendations are made for early intervention for low birthweight male twins. The study is consistent with recent follow-up studies of very-low-birthweight singletons, indicating male disadvantage in cognitive outcome. While there is some genetic component to SGA, it does constitute a potentially major contribution to common environmental effects that must be considered in twin-based genetic analyses.